ACUTE ORAL TOXICITY ASSESSMENT OF THE ETHANOL EXTRACT OF HOLOTHURIA ATRA IN MICE - SALIM HANAFI, PANDU; SUTRISNO, AJI; MURNIASIH, TUTIK; HARIJONO; YUNOVILSA PUTRA, MASTERIA; UNTARI, FEBRIANA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to evaluate the toxicological potential of the ethanol extract of Holothuria atra through the acute oral toxicity – acute toxic class method. Methods: The sample was immersed in ethanol for 72 h at room temperature and repeated 3 times. The extracts were evaporated using a vacuum rotary evaporator. The identification of compounds in the ethanol extract of H. atra was carried out using liquid chromatography–mass spectrometry (LCMS) analysis. The acute toxicity test was examined the effects of treating male mice with the ethanol extract of H. atra at 300 and 2000 mg/kg by oral administration for 14 days. On the past day of the toxicity test, liver of all experimental animals was taken for histopathological testing. Results: LCMS analysis showed that the ethanol extract of H. atra is contained polar compounds (chlorogenic acid, coumaric acid, a glycosaminoglycan, and holothurin) and non-polar compounds (fatty acids). Acute toxicity study was performed at a dose of 300 and 2000 mg/kg for 14 consecutive days. No deaths or behavioral changes were observed during the administration of both doses. Histopathological test results on the liver showed a few changes at doses of 2000 mg/kg. Conclusions: The LD50 is equal to 5000 mg/kg and the ethanol extracts of H. atra can be classified as practically nontoxic. However, further studies are required to proceed to clinical studies in humans.